Improved stereo matching algorithm based on census transform and dynamic histogram cost computation - Kadmin, Ahmad Fauzan; Hamzah, Rostam Affendi; Abd Manap, Nurulfajar; Hamid, Mohd Saad; Abd Gani, Shamsul Fakhar (IJETAE Publication House, 2021)
Stereo matching is a significant subject in the stereo vision algorithm. Traditional taxonomy composition consists of several issues in the stereo correspondences process such as radiometric distortion, discontinuity, and low accuracy at the low texture regions. This new taxonomy improves the local method of stereo matching algorithm based on the dynamic cost computation for disparity map measurement. This method utilised modified dynamic cost computation in the matching cost stage. A modified Census Transform with dynamic histogram is used to provide the cost volume. An adaptive bilateral filtering is applied to retain the image depth and edge information in the cost aggregation stage. A Winner Takes All (WTA) optimisation is applied in the disparity selection and a left-right check with an adaptive bilateral median filtering are employed for final refinement. Based on the dataset of standard Middlebury, the taxonomy has better accuracy and outperformed several other state-of-the-art algorithms.